Analisis Tingkat dan Sebaran Bencana Tanah Longsor di Kabupaten Bengkulu Tengah: Analysis of the Level and Distribution of Landslide Disasters in Bengkulu Tengah Regency - Muhammad Latif; Andriani Andriani; Abdul Hakam (Bentang : Jurnal Teoritis dan Terapan Bidang Rekayasa Sipil, 2023)
The confluence of the three largest plates in the world between the Indo-Australian, Eurasian, and Pacific plates makes Indonesia a potential area for landslides. A landslide is the movement of a mass of soil or geology through a sliding plane down a slope. Bengkulu Tengah Regency, which is in Bengkulu Province, is an area prone to landslides, this can be seen based on previous events, which have caused people to experience loss of property and loss of life. Distribution Analysis of landslides is a method used to identify areas with potential levels of landslides starting from low to very high, which allows people to be more vigilant. The purpose of this study is to determine the distribution of landslide susceptibility and dominant factors that influence the level of landslide potential. The research method was carried out by giving weights and scoring with reference to Puslittanak. The making of landslide map was obtained from the results of overlaying secondary data such as DEM, distribution of land cover, distribution of rainfall, geological distribution, and distribution of soil types using the ArcGIS 10.7 application. The results showed that the level of landslides distribution in Bengkulu Tengah Regency was dominated by the distribution level of moderate landslides covering an area of ​​73455 Ha with a percentage of 60%. Areas that have a very high distribution of landslides are in four sub-districts consisting of Taba Penanjung, Meringgi Kelindang, Meringgi Sakti, and Pematang Tiga sub-districts with an area of ​​8948 Ha with a percentage of 7%. The rainfall map distribution had the highest value, which the most dominant factor in the process of landslide occurrence.